Child or Grown-up: Language Universals and Language Particula - Arakelyan, Rouzanna (Armenian Folia Anglistika, 2005)
Language is a means of human cognitive activity. The knowledge of the natural process of the acquisition of each language, namely of a foreign one, is highly necessary in language learning process. The record of the characteristics of child language development acquires much significance in this regard. Evidently, each child is unique. However, the sequence of the development stages of native and foreign languages is almost the same and quite predictable, while the psycholinguistic investigation of a foreign language learning among grown-ups demonstrates evident differences. The acquisition of a foreign language differs not only in the content of the material studied, but also in the new linguistic nature of the coordination of the knowledge.